Analysis of the assortment and availability hepatotropic drugs on the pharmaceutical market of Ukraine - Геруш, Олег Васильевич; Ткачева, Оксана Витальевна (ScienceRise: Pharmaceutical Science, 2016)
The aim of this work was the analysis of the assortment, consumption and socio-economic availability hepatotropic drugs (HD) on the pharmaceutical market of Ukraine for the period 2012–2015. Methods: monitoring, system and graphics. An analysis of the range and value of products held according to the system «Pharmstandard» company "Morion". Results. The dynamics of the HD showed instability of this market segment and dependence on the US dollar, which is directly connected with the economic situation in the country and the purchasing power of the population. During the 2012–2015 on Ukraine's pharmaceutical market was a gradual increase in the number of cheap domestic drugs and the reduction of expensive imported drugs. The results of HD consumption as a whole and in subgroups showed that during the analyzed period, the demand for HD was unstable. From 2012 to 2013 in most subgroups showed a significant increase in the implementation of the HD and then from 2013 to 2014 – its decline. The largest decline occurred for the consumption of INN ornithine oksoglurat (A05BA06), whose cost varies greatly – from 114.94 grn. (2012) up to 2383.40 grn. (2015). Analysis of the economic availability revealed that the majority of the HD in terms Ca.s. in % refers to high available, allowing consumers to choose the medicament of its financial capabilities. Low availability are mainly hepatotropic preparations ornithine oxoglutarate and ursodeoxycholic acid. Conclusions. Assortment hepatotropic drugs in the pharmaceutical market of Ukraine is enough. The proportion of products of domestic production gradually increased. Prices of drugs during 2012–2015 increased in 3–4 times. Despite the rise in prices is still the majority of the HD are highly available for the people of Ukraine